2009
DOI: 10.4012/dmj.28.234
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation ability of carbonate apatite-collagen scaffolds with different carbonate contents

Abstract: Hydroxyapatite and carbonate apatites with different carbonate contents were synthesized, mixed with atelocollagen, and made into sponge scaffolds. The scaffolds were implanted into the bone sockets of the femurs of male New Zealand white rabbits for 2, 3, 12 and 24 weeks. carbonate apatite-collagen scaffold with 4.8 wt% carbonate content appeared to have similar crystallinity and chemical composition to human bone. When the scaffolds were implanted into the rabbit femurs, histological observation indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Studies have shown the level of CO3 in apatite to be important for bone formation. The concentration of 4.8 wt% CO3 appeared to have a similar crystallinity and chemical composition to human bone and had the highest bone formation ability 12) . The apatite synthesized in this study showed similar chemical composition to human enamel and dentin (Table 2) which may be an advantage in adhesion and biocompatibility to tooth structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the level of CO3 in apatite to be important for bone formation. The concentration of 4.8 wt% CO3 appeared to have a similar crystallinity and chemical composition to human bone and had the highest bone formation ability 12) . The apatite synthesized in this study showed similar chemical composition to human enamel and dentin (Table 2) which may be an advantage in adhesion and biocompatibility to tooth structure.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of incorporating Mg and CO 3 into apatite would increase the extent of dissolution and may enhance the biological response 14) . A study of the effect of CO3 on bone formation suggested that CO3Ap-collagen scaffolds with CO3 content similar to that of human bone would have an optimal bone forming ability 12) . This was confirmed by an in vivo study 8) , which also reported that divalent ions affected cell adhesion by interacting with integrins at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to overcome these disadvantages is to design composite substances that combine the strengths of different materials and minimize their drawbacks. The incorporation of chitosan with calcium phosphate, such as hydroxyapatite (HA), β-tricalcium phosphate (β-TCP), and carbonate apatite (CA) [37][38][39][40][41] , could improve the mechanical properties of the material and enhance its biological properties. HA and β-TCP have been widely applied in bone tissue regeneration due to their interesting properties, mainly those of biocompatibility, osteoconductivity, and osteoinductivity [37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, this material is absorbed before sufficient new bone formation [37][38][39][40] . Among these calcium phosphates, CA has been reported to have an appropriate absorbance time period and good bone formation ability 39,41) . Therefore, we focused on combining chitosan as an organic and resorbsable material with CA in order to obtain a scaffold with an appropriate absorbance time period and to enhance bone formation ability.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the interrelation of CO3 2-contents in apatite crystals and biocompatibility, hydroxyapatite and CO3apatites with different carbonate contents were synthesized 6) , mixed with atelocollagen, and made into sponge scaffolds 7) . The scaffolds were implanted into the bone sockets of the femurs of male New Zealand white rabbits.…”
Section: Effect Of Co3 2-ions On Bone Formationmentioning
confidence: 99%